Power management strategy based sugeno fuzzy logic rules in an electric wheelchair - Abdeselem, Chakar; Othmane, Abdelkhalek; Brahim, Gasbaoui; Amine, Soumeur Mohammed; Oussama, Hafsi; Amine, Hartani Mohammed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Power management in multi-power supply electrical systems to manage the general system behavior is essential to improve autonomy and efficiency. In this paper, a proposed fuzzy-logic power management-based sugeno rule is applied in a hybrid PV/battery electric wheelchair to ameliorate the battery life cycle and the overall autonomy. Besides, the increment conductance INC MPPT is used to maximize PVpower. The electric wheelchair's general topology comprises photovoltaic energy resources as the main source and the battery energy storage system device as the auxiliary source. This hybrid power source system supplied the electric wheelchair composed two permanent magnet DC motors controlled by a PI controller. MATLAB/Simulink program is used to implement the overall control scheme. The simulation results that were obtained and the detailed study demonstrate the feasibility and performance of this intelligent strategy.